Letter from the editor (2016)
Dear readers. The Earth Sciences Research Journal has been recently flooded with dozens of good papers expecting to be published. Thanks to you, readers, reviewers, authors for your trust. We are continuously working to improve our editorial processes. The trend topics of those papers go from gas and petroleum exploitation, land use, geological hazards, to sustainable development, environmental protection and optimization of operation techniques. Without forgetting the basic research. All those subjects are welcome in Earth Sciences Research Journal. Proudly, we remark our journal, your journal, as the natural stage for the debate between economic development and sustainable development. There is no a better referee for this discussion than education entities. If your manuscript put lights on this important subjects, do not hesitate to submit it. Is this not a minor topic! Nowadays, every political decision, every policy designed, every industrial and human activity are seen through the lens of the Environmental Awareness. We can not quit on this responsibility. As an example of how important those topics are, during the coming days, US President Barack Obama is going to enact a law expanding the protection areas in Hawaii in close four times the current size. It means longlines fishing operators will not be permitted in the 582581 square miles; neither the seabed mining in a region with rich deposits of manganese, nickel, zinc, cobalt, and titanium. Similar decisions have been taken in Chile and Costa Rica, this last one with a 26% of its land territory protected as a natural park. Just talking about some cases in this side of the world, where we are more familiar with. The next meeting of Geological Society of America, taking place in Denver, on September, will hand on this same topics. Are the extracting and exploitation of resource prohibitions the solution to environmentalism? Welcome all your papers cracking this nut.